Buddhist Leadership for the Local Leaders in Suratthani, Thailand - Phuakkhong, Chaiwat (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on analyzing Buddhist leadership for the local leaders in Suratthani province, Thailand by trying to demonstrate perspectives through a 14 years’ observation of the administration of local administrative organizations in Suratthani towards the good governance with the principles of leadership theory and Buddhist leadership, a critical factor for success of local leaders to develop the concepts and theory of participation to enhance the good governance. The results found that the guidelines for the good governance of Buddhist leadership for local leaders in Suratthani consisted of (1) Cognitive intelligence, having foresight and wide vision to understanding the condition of event, and advance with knowledge and initiative to solve problems logically. (2) Having faith, leaders must have public mind and paying attention to the benefits of public. (3) Adheres to the rule of law in decision making as a tool to analyze the situation precisely to be reliable in work and not against the law. (4) Honesty, good quality of leaders must be honest and having a good conscience as a guideline for good conduct. (5) Transparency, leaders must be transparent and honest to the people. (6) Observe the 5 precepts and behave as a good role example for subordinates to follow to nourish the mind and career advancement under the concept of using economical and worthwhile resources for administration.